Secondary battery electrolyte, secondary battery, battery module, battery pack and electric device
Patent Information
- Application Number
- CN202280096221.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2024-12-27
AI Technical Summary
The performance of existing secondary batteries deteriorates and safety risks are serious in high-temperature environments, mainly because the electrolyte easily decomposes at high temperatures and reacts with the negative electrode to produce serious gas.
Using an electrolyte solution containing electrolyte salt, solvent and polyether, the polyether is generated through in-situ polymerization in the electrolyte solution to provide a polymer skeleton, reduce the dynamic activity of solvent molecules, reduce the direct contact between the positive and negative electrodes and the solvent, and suppress high-temperature production. gas phenomenon. Suitable lithium ions and additives such as lithium hexafluorophosphate and lithium tetrafluoroborate work synergistically to improve the high-temperature cycle performance of the battery.
It effectively reduces the gas production of secondary batteries at high temperatures, improves the safety performance and high-temperature cycle performance of the battery, and broadens the operating temperature range of the battery.
Smart Images

Figure CN119213599A_ABST
Abstract
Description
Secondary battery electrolyte, secondary battery, battery module, battery pack and power-consuming device Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery electrolyte, a secondary battery, a battery module, a battery pack, and an electrical device. Background Art
[0002] As society develops, various issues, including energy shortages and environmental pollution, are becoming increasingly prominent. To achieve the goal of a sustainable society, researchers are turning their attention to secondary batteries. Secondary batteries are the preferred energy storage system for portable electronics and electric vehicles, but they suffer from significant performance degradation and serious safety risks in high-temperature environments.
[0003] The electrolyte, the medium for transferring secondary ions between the positive and negative electrodes, has a direct impact on the performance of secondary batteries at high temperatures. Existing electrolytes are prone to decomposition at high temperatures and react with the negative electrode, producing severe gassing. Therefore, developing an electrolyte with high high-temperature stability to improve the high-temperature performance of batteries has become a pressing issue for those skilled in the art.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide an electrolyte to reduce the high-temperature gas generation phenomenon of the battery and expand the applicable environment of the battery.
[0006] A first aspect of the present application provides a secondary battery electrolyte comprising an electrolyte salt, a solvent, and a polyether.
[0007] Polyether can provide a polymer skeleton in the electrolyte, reduce the kinetic activity of solvent molecules in the electrolyte, reduce direct contact between the positive and negative electrodes and the solvent, inhibit the gas production of secondary batteries during high-temperature cycling, and improve the safety performance of the battery at high temperatures.
[0008] In some embodiments, the electrolyte contains lithium ions, and the mass content of the lithium ions is 0.05% to 0.46%, based on the total mass of the electrolyte.
[0009] Lithium ion with appropriate mass content can further improve the room temperature cycle performance and high temperature cycle performance of the battery through synergistic effect, and reduce the high temperature gas production of the battery.
[0010] In any embodiment, the mass content of the polyether is 10% to 70%, based on the total mass of the electrolyte.
[0011] The appropriate mass content of polyether makes the electrolyte have a suitable viscosity, and the battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature performance, and low high temperature gas production, which helps to broaden the operating temperature of the battery.
[0012] In any embodiment, the polyether is generated by in-situ polymerization of a cyclic ether compound in an electrolyte under the initiation of a Lewis acid.
[0013] By in-situ polymerization in the electrolyte to generate polyether, the polyether is evenly distributed in the electrolyte, which can effectively reduce the high-temperature gas generation phenomenon of the battery.
[0014] In any embodiment, the Lewis acid comes from an additive in the electrolyte, and the additive comprises one or more selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate.
[0015] Under certain conditions, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate can generate Lewis acids that can be used to initiate the in-situ polymerization of cyclic ether compounds to form polyethers. These additives can also provide a certain amount of lithium ions, synergistically improving the battery's room-temperature and high-temperature cycling performance while reducing high-temperature gassing.
[0016] In any embodiment, the Lewis acid comes from an additive in the electrolyte, and the additive comprises one or two selected from lithium hexafluorophosphate and lithium tetrafluoroborate.
[0017] Suitable additives can improve the room temperature cycle performance and high temperature cycle performance of the battery and reduce the high temperature gas production of the battery.
[0018] In any embodiment, the mass content of the additive added is 1% to 10% based on the total mass of the electrolyte.
[0019] The appropriate mass content of additives makes the electrolyte have suitable viscosity and good ionic conductivity. The battery has excellent first coulombic efficiency, room temperature cycle performance, high temperature cycle performance and low high temperature gas production, which helps to further broaden the operating temperature of the battery.
[0020] In any embodiment, the mass content of the additive added is 2% to 6% based on the total mass of the electrolyte.
[0021] Additives with appropriate mass content can improve the battery's initial coulombic efficiency, room temperature cycle performance and high temperature cycle performance, and reduce the battery's high temperature gas production.
[0022] In any embodiment, the cyclic ether compound comprises one or more selected from 1,3-dioxolane, ethylene glycol diglycidyl ether, 1,4-butanediol glycidyl ether, 1,2,3,4-diepoxybutane, tetrahydrofuran, methyltetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
[0023] The conditions for the ring-opening polymerization of the above-mentioned cyclic ether compounds are mild, which is conducive to the occurrence of in-situ polymerization reactions. By generating polyether with an appropriate mass content, the electrolyte has a suitable viscosity and good ionic conductivity. The battery has excellent first coulombic efficiency, room temperature cycle performance, high temperature cycle performance and low high-temperature gas production, which helps to further broaden the battery's operating temperature.
[0024] In any embodiment, the cyclic ether compound comprises one or more selected from 1,3-dioxolane, tetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
[0025] In any embodiment, the solvent comprises a chain ether compound.
[0026] Chain ether compounds impart suitable viscosity and excellent ionic conductivity to the electrolyte. Chain ether compounds share the same ether bond with polyethers, improving the compatibility of the electrolyte system. Using chain ether compounds as solvents can further enhance the uniformity of the polyether distribution in the electrolyte, improving the battery's initial coulombic efficiency, room-temperature cycling performance, and high-temperature cycling performance, while reducing high-temperature gas production. This improves the battery's electrochemical and safety performance, broadening its operating temperature range.
[0027] In any embodiment, the solvent comprises one or more selected from ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether.
[0028] In any embodiment, based on the total volume of the solvent in the electrolyte, the volume content of the cyclic ether compound added is 1 / 5-5.
[0029] The appropriate volume content of cyclic ether compounds enables the electrolyte to have an appropriate mass content of polyether, which can ensure that the electrolyte has suitable viscosity and excellent ionic conductivity, help reduce high-temperature gas production of the battery, and ensure that the battery has excellent first coulombic efficiency, room temperature cycle performance and high-temperature cycle performance.
[0030] In any embodiment, based on the total volume of the solvent in the electrolyte, the volume content of the cyclic ether compound added is 1 / 3-3.
[0031] The appropriate volume content of cyclic ether compounds enables the electrolyte to have an appropriate mass content of polyether, which can ensure that the electrolyte has suitable viscosity and excellent ionic conductivity, help reduce high-temperature gas production of the battery, and ensure that the battery has excellent first coulombic efficiency, room temperature cycle performance and high-temperature cycle performance.
[0032] In any embodiment, the electrolyte salt includes at least one of a first sodium salt and a second sodium salt, the first sodium salt includes one or more selected from sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, and sodium trifluoroacetate, and the anion structure of the second sodium salt includes at least one of the structures shown in Formula I and Formula II.
[0033]
[0034] wherein R1, R2, and R3 are each independently fluorine or a C1-C6 fluoroalkyl group.
[0035] The electrolyte contains the first sodium salt or the second sodium salt, and the battery has low high-temperature gas generation.
[0036] In any embodiment, the mass content of the first sodium salt in the electrolyte is 2% to 40% based on the total mass of the electrolyte.
[0037] The appropriate mass content of the first sodium salt ensures reversible deposition and stripping of metal ions at the negative electrode, making it particularly suitable for negative-electrode-free sodium batteries. Furthermore, the appropriate mass content of the first sodium salt imparts an appropriate electrolyte viscosity and excellent ionic conductivity, improving the battery's initial coulombic efficiency and room-temperature cycling performance while reducing high-temperature gassing.
[0038] In any embodiment, the second sodium salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethanesulfonyl)imide.
[0039] The anions in the second sodium salt can be reduced on the surface of the negative electrode to form sulfur-containing compounds and nitrogen-containing compounds. The sulfur-containing compounds and nitrogen-containing compounds can effectively passivate the negative electrode, further reduce the occurrence of side reactions between the negative electrode and the electrolyte, improve the high-temperature cycle performance of the battery, reduce the high-temperature gas production of the battery, and improve the electrochemical performance and safety performance of the battery.
[0040] In any embodiment, the mass content of the second sodium salt in the electrolyte is 1% to 10% based on the total mass of the electrolyte.
[0041] The second sodium salt with an appropriate mass content helps to form a structurally stable and evenly distributed SEI, improves the high-temperature cycle performance of the battery, and reduces the high-temperature gas production of the battery.
[0042] In any embodiment, the viscosity of the electrolyte at 25° C. is less than 1300 mPa·s.
[0043] The electrolyte has an appropriate viscosity, which can not only ensure the excellent ionic conductivity of the electrolyte, but also ensure that the electrolyte has good wettability to the electrodes, so that the battery has both excellent electrochemical properties and safety performance.
[0044] A second aspect of the present application provides a method for preparing a secondary battery electrolyte, comprising the following steps:
[0045] Adding an additive and a cyclic ether compound to a composition comprising an electrolyte salt and a solvent, wherein the additive is a Lewis acid or a Lewis acid precursor;
[0046] The in-situ polymerization is carried out for at least 24 hours to obtain a secondary battery electrolyte.
[0047] Lewis acids or Lewis acid precursors are used to initiate in-situ polymerization of cyclic ether compounds, generating a uniformly distributed polyether in the electrolyte. The polyether provides a polymer backbone in the electrolyte, reducing the molecular dynamics activity of the solvent, minimizing direct contact between the positive and negative electrodes and the solvent, and inhibiting gas generation during high-temperature cycling of the secondary battery. This improves the battery's high-temperature gassing behavior and enhances its safety at high temperatures.
[0048] In any embodiment, the additive comprises one or more selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate.
[0049] Under certain conditions, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate can generate Lewis acids that can initiate the polymerization of cyclic ether compounds. They can also provide a certain amount of lithium ions, improving the battery's room-temperature and high-temperature cycling performance and reducing high-temperature gassing.
[0050] In any embodiment, the additive comprises one or two selected from lithium hexafluorophosphate and lithium tetrafluoroborate.
[0051] Suitable additives can improve the room temperature cycle performance and high temperature cycle performance of the battery and reduce the high temperature gas production of the battery.
[0052] In any embodiment, the mass content of the additive added is 1% to 10% based on the total mass of the electrolyte.
[0053] With the appropriate mass content of additives, the electrolyte has appropriate viscosity and good ionic conductivity, the battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance and low high temperature gas production, the battery has excellent electrochemical performance and safety performance, and broadens the battery's operating temperature.
[0054] In any embodiment, the mass content of the additive added is 2% to 6% based on the total mass of the electrolyte.
[0055] Additives with appropriate mass content can improve the battery's initial coulombic efficiency, room temperature cycle performance and high temperature cycle performance, and reduce the battery's high temperature gas production.
[0056] In any embodiment, the cyclic ether compound comprises one or more selected from 1,3-dioxolane, ethylene glycol diglycidyl ether, 1,4-butanediol glycidyl ether, 1,2,3,4-diepoxybutane, tetrahydrofuran, methyltetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
[0057] Suitable cyclic ether compounds have mild ring-opening polymerization conditions, which are conducive to the occurrence of in-situ polymerization reactions to generate polyethers with appropriate mass content. The electrolyte has appropriate viscosity and good ionic conductivity. The battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance and low high temperature gas production. The battery has excellent electrochemical properties and safety performance, which broadens the battery's operating temperature.
[0058] In any embodiment, the cyclic ether compound comprises one or more selected from 1,3-dioxolane, tetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
[0059] In any embodiment, based on the total volume of the solvent in the electrolyte, the volume content of the cyclic ether compound added is 1 / 5-5.
[0060] The appropriate volume content of cyclic ether compounds ensures that the electrolyte has an appropriate mass content of polyether, while ensuring that the electrolyte has appropriate viscosity and excellent ionic conductivity, reducing high-temperature gas production of the battery, and ensuring that the battery has excellent first coulombic efficiency, room temperature cycle performance and high-temperature cycle performance.
[0061] In any embodiment, the volume content of the cyclic ether compound added is 1 / 3-3 based on the total volume of the solvent in the electrolyte.
[0062] The appropriate volume content of cyclic ether compounds ensures that the electrolyte has an appropriate mass content of polyether, while ensuring that the electrolyte has excellent viscosity and ionic conductivity, which can further reduce the high-temperature gas production of the battery, while ensuring that the battery has excellent first coulombic efficiency, room temperature cycle performance and high-temperature cycle.
[0063] A third aspect of the present application provides a secondary battery, comprising an electrolyte, wherein the electrolyte comprises the electrolyte of the first aspect or the electrolyte prepared by the preparation method of the second aspect.
[0064] In any embodiment, the secondary battery includes at least one of a sodium ion battery and a lithium ion battery.
[0065] In any embodiment, the secondary battery is a negative electrode-less sodium metal battery.
[0066] In a negative electrode-free sodium battery, the metallic sodium on the negative electrode is produced during subsequent cycles. The sodium ion battery has no voltage before the first charge, so the sodium ion battery can be stored for a long time without self-discharge. Even if the battery is short-circuited, no current will be generated, which can further improve the safety of the battery.
[0067] In any embodiment, the secondary battery includes a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector and a primer layer formed on at least a portion of a surface of the negative electrode current collector.
[0068] The conductive primer layer has the characteristic of low metal nucleation potential, which can effectively improve the deposition / dissolution performance of the metal. At the same time, it can also improve the huge volume changes caused by the deposition / dissolution process of the metal to the battery cell, stabilize the battery cell structure, improve the high-temperature cycle performance of the battery, and reduce the high-temperature gas production of the battery.
[0069] In any embodiment, the primer coating is a conductive carbon coating.
[0070] Conductive carbon coating can effectively reduce the overpotential of metal deposition, inhibit the formation of metal dendrites, improve the room temperature cycle performance and high temperature cycle performance of the battery, and reduce the high temperature gas production of the battery.
[0071] In any embodiment, the surface density of the conductive carbon coating is 5 to 50 g / m 2 .
[0072] A suitable range of basecoat surface density can optimize metal deposition, improve the battery's high-temperature and room-temperature cycling performance, and reduce high-temperature gassing. At the same time, a suitable range of basecoat surface density can increase the battery's energy density and meet battery usage requirements.
[0073] A fourth aspect of the present application is a battery module, comprising the secondary battery of the third aspect.
[0074] A fifth aspect of the present application provides a battery pack comprising at least one of the secondary battery of the third aspect and the battery module of the fourth aspect.
[0075] A sixth aspect of the present application provides an electrical device comprising at least one of the secondary battery of the third aspect, the battery module of the fourth aspect, and the battery pack of the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0077] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;
[0078] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0079] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0080] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;
[0081] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0082] Reference numerals:
[0083] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0084] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0085] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0086] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0087] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0088] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0089] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0090] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0091] When secondary batteries are used or stored at high temperatures, the activity of the reaction between the positive and negative electrodes and the electrolyte increases, the heat released by the reaction increases significantly, and a large amount of gas is generated, causing the battery to easily expand in volume. In severe cases, it may also cause a short circuit inside the battery, seriously affecting the safety performance of the battery.
[0092] [Electrolyte]
[0093] Based on this, the present application provides an electrolyte solution comprising an electrolyte salt, a solvent and a polyether.
[0094] As used herein, the term "electrolyte" refers to the composition, including solvent and electrolyte salt, that establishes an ion-conducting pathway between the positive and negative electrodes within a battery while simultaneously blocking the flow of electrons. The electrolyte herein can be in any form, such as a low-viscosity, flowable liquid or a high-viscosity gel.
[0095] As used herein, the term "electrolyte salt" refers to a compound composed of metal cations and anions that is electrically conductive in aqueous solution or in a molten state.
[0096] As used herein, the term "polyether" refers to a class of macromolecules containing ether (-OCO-) segments in the polymer backbone, including polyalkylene oxides, aromatic polyethers, epoxy resins, acetal resins, polyethersulfones, and polyetherimides. It is understood that the degree of polymerization of polyethers is not limited herein; polyethers can be either polymers or oligomers.
[0097] In some embodiments, the polyether is a polyalkylene oxide.
[0098] As used herein, the term "polyalkylene oxide" refers to a polymer obtained by ring-opening homopolymerization or copolymerization of alkylene oxides in the presence of a catalyst. Examples of polyalkylene oxides include polyethylene oxide, polypropylene oxide, polytetrahydrofuran, polytetrahydropyran, poly-1,3-dioxolane, poly-1,4-dioxane, and ethylene oxide-propylene oxide copolymers.
[0099] The addition of polyether to the electrolyte provides a polymer skeleton, which can have a binding effect on the solvent molecules, thereby reducing the kinetic activity of the solvent molecules in the electrolyte, reducing the direct contact between the positive and negative electrodes and the solvent, reducing the possibility of chemical reactions between the positive and negative electrodes and the solvent, inhibiting the generation of gas during high-temperature cycling of the secondary battery, improving the high-temperature gas production performance of the secondary battery, and improving the safety performance of the secondary battery at high temperatures.
[0100] In some embodiments, the electrolyte contains lithium ions, and the mass content of lithium ions is 0.05% to 0.46%, based on the total mass of the electrolyte. In some embodiments, the mass content of lithium ions can be selected from any one of 0.05% to 0.1%, 0.05% to 0.2%, 0.05% to 0.3%, 0.05% to 0.4%, 0.4% to 0.46%, 0.1% to 0.2%, 0.1% to 0.3%, 0.1% to 0.4%, 0.1% to 0.46%, 0.2% to 0.3%, 0.2% to 0.4%, 0.2% to 0.46%, 0.3% to 0.4%, and 0.3% to 0.46%, based on the total mass of the electrolyte.
[0101] Lithium ion with appropriate mass content can improve the battery's room temperature cycle performance and high temperature cycle performance, and reduce the battery's high temperature gas production.
[0102] Taking sodium metal batteries as an example, the introduction of lithium ions can also effectively inhibit the growth of sodium dendrites during the sodium metal deposition process. During the charging process of the sodium metal battery, an electrochemical reaction will occur at the negative electrode in which sodium ions gain electrons and are reduced to sodium metal. In the early stage of the reaction, sodium metal is unevenly deposited on the surface of the current collector to form dendrites, and the dendrite tips have a higher negative charge density due to the tip effect. Lithium ions and sodium ions are both monovalent positive cations with a unit positive charge. However, lithium ions have a smaller radius and therefore have a higher positive charge density. They will be distributed at the dendrite tips before sodium ions, effectively reducing the continued deposition of sodium ions at the tips of sodium dendrites, inhibiting the growth of sodium dendrites, and thus greatly improving the cycle performance of sodium metal batteries.
[0103] In some embodiments, the mass content of the polyether is 10% to 70%, based on the total mass of the electrolyte. In some embodiments, the mass content of the polyether can be selected from any one of 10% to 20%, 10% to 30%, 10% to 40%, 10% to 50%, 10% to 60%, 10% to 70%, 20% to 30%, 20% to 40%, 20% to 50%, 20% to 60%, 20% to 70%, 30% to 40%, 30% to 50%, 30% to 60%, 30% to 70%, 40% to 50%, 40% to 60%, 40% to 70%, 50% to 60%, 50% to 70%, and 60% to 70%, based on the total mass of the electrolyte.
[0104] The appropriate mass content of polyether makes the electrolyte have appropriate viscosity and excellent ionic conductivity, the battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature performance, the battery has low high temperature gas production, and widens the battery's operating temperature.
[0105] In some embodiments, the polyether is generated by in-situ polymerization of a cyclic ether compound in an electrolyte under the initiation of a Lewis acid.
[0106] As used herein, the term "cyclic ether compound" refers to a product in which the hydrogen of the hydroxyl group of an alcohol or phenol is replaced by a hydrocarbon group, with the carbon atoms and oxygen atoms in the product forming a cyclic structure. By way of example, the cyclic ether compound may be a three-membered ring, a four-membered ring, a five-membered ring, or a six-membered ring containing an ether bond, including but not limited to ethylene oxide, propylene oxide, butylene oxide, tetrahydrofuran, tetrahydropyran, 1,3-dioxolane, 1,4-dioxane, ethylene glycol diglycidyl ether, 1,4-butanediol glycidyl ether, 1,2,3,4-diepoxybutane, and methyltetrahydrofuran.
[0107] In this article, the term "Lewis acid" refers to a molecule, ion, or atomic group that can accept an external electron pair, i.e., an electron docking acceptor. Lewis acids primarily include: metal cations in coordination compounds; some molecules and ions whose central atoms, despite satisfying an octet, can expand their coordination sphere to accommodate more electron pairs; some molecules and ions whose central atoms satisfy an octet but can accept additional electron pairs through valence shell electron rearrangement; and certain closed-shell molecules that accommodate external electron pairs through their antibonding molecular orbitals.
[0108] In some embodiments, the Lewis acid can be a cation or metal ion, such as a sodium ion, an alkyl cation, or a nitro cation.
[0109] In some embodiments, the Lewis acid can be an electron-deficient compound, such as boron trifluoride, phosphorus pentafluoride, aluminum trichloride, sulfur trioxide.
[0110] As used herein, the term "in situ polymerization" means that the polymer is prepared by polymerization of reactive monomers in an electrolyte.
[0111] In some embodiments, the Lewis acid is added directly to the electrolyte in the form of an additive. In some embodiments, the Lewis acid is generated by decomposition of the additive in the electrolyte.
[0112] Polyethers generated by in-situ polymerization can effectively overcome the problem of poor polymer solubility in electrolytes. This process achieves uniform distribution of the polyether within the electrolyte, increasing direct interaction with the solvent molecules in the electrolyte. This in turn reduces direct contact between the solvent molecules in the electrolyte and the positive and negative electrodes, effectively mitigating high-temperature gassing in the battery. Furthermore, in-situ polymerization can occur in situ within the secondary battery system after electrolyte injection, effectively avoiding the processing difficulties associated with excessive electrolyte viscosity and difficult battery assembly caused by the addition of polyether. This allows for optimized battery performance and improved production efficiency without changing the existing battery production process.
[0113] In some embodiments, the Lewis acid comes from an additive in the electrolyte, and the additive comprises one or more selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate.
[0114] In this article, the term "additive" refers to a component present in a relatively small amount in the electrolyte, which can be a gas, liquid, or solid. Conceptually, the difference between additives, solvents, and electrolyte salts lies only in their content in the electrolyte.
[0115] Under certain conditions, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate decompose to produce Lewis acids, which are used to initiate the polymerization of cyclic ether compounds to form polyethers. These lithium salts also provide a certain amount of lithium ions, which can improve the battery's room-temperature and high-temperature cycling performance and reduce high-temperature gassing.
[0116] In some embodiments, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate are thermally decomposed at a certain temperature to generate Lewis acids.
[0117] In some embodiments, lithium hexafluorophosphate is thermally decomposed, and the products include Lewis acid phosphorus pentafluoride and lithium fluoride.
[0118] In some embodiments, lithium tetrafluoroborate is thermally decomposed, and the products include Lewis acid boron trifluoride and lithium fluoride.
[0119] In some embodiments, lithium perchlorate is thermally decomposed and the product includes the Lewis acid lithium chloride.
[0120] In some embodiments, lithium difluorooxalatoborate is thermally decomposed, and the products include Lewis acid boron trifluoride and lithium fluoride.
[0121] In some embodiments, the Lewis acid comes from an additive in the electrolyte, and the additive comprises one or two selected from lithium hexafluorophosphate and lithium tetrafluoroborate.
[0122] Lithium hexafluorophosphate and lithium tetrafluoroborate readily decompose under mild thermal conditions, facilitating in-situ polymerization within the electrolyte system and ensuring reaction reliability. Appropriate additives can improve both room-temperature and high-temperature cycling performance and reduce gas production at high temperatures.
[0123] In some embodiments, based on the total mass of the electrolyte, the mass content of the additives added is 1% to 10%. In some embodiments, based on the total mass of the electrolyte, the mass content of the additives added can be selected from 1% to 2%, 1% to 3%, 1% to 4%, 1% to 5%, 1% to 6%, 1% to 7%, 1% to 8%, 1% to 9%, 1% to 10%, 2% to 3%, 2% to 4%, 2% to 5%, 2% to 6%, 2% to 7%, 2% to 8%, 2% to 9%, 2% to 10%, 3% to 4%, 3% to 5%, 3% to 6%, 3% to 7%, 3% to 8%, 3% to 9%, 3% to 10%, 4% to 5%, Any one of 4% to 6%, 4% to 7%, 4% to 8%, 4% to 9%, 4% to 10%, 5% to 6%, 5% to 7%, 5% to 8%, 5% to 9%, 5% to 10%, 6% to 7%, 6% to 8%, 6% to 9%, 6% to 10%, 7% to 8%, 7% to 9%, 7% to 10%, 8% to 9%, 8% to 10%, and 9% to 10%.
[0124] The appropriate mass content of additives makes the electrolyte have suitable viscosity and good ionic conductivity. The battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance and low high temperature gas production, which can further broaden the operating temperature of the battery.
[0125] In some embodiments, the mass content of the additive added is 2% to 6% based on the total mass of the electrolyte. In some embodiments, the mass content of the additive added is any one of 2% to 3%, 2% to 3%, 2% to 4%, 2% to 5%, 2% to 6%, 3% to 4%, 3% to 5%, 3% to 6%, 4% to 5%, 4% to 6%, and 5% to 6% based on the total mass of the electrolyte.
[0126] Additives with appropriate mass content can improve the battery's initial coulombic efficiency, room temperature cycle performance and high temperature cycle performance, and reduce the battery's high temperature gas production.
[0127] In some embodiments, the cyclic ether compound comprises one or more selected from 1,3-dioxolane, ethylene glycol diglycidyl ether, 1,4-butanediol glycidyl ether, 1,2,3,4-diepoxybutane, tetrahydrofuran, methyltetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
[0128] Suitable cyclic ether compounds are easy to undergo ring-opening polymerization, which is conducive to the occurrence of in-situ polymerization reactions in the electrolyte, generating polyethers with appropriate mass content, so that the electrolyte has suitable viscosity and good ionic conductivity. The battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance and low high temperature gas production, which can further broaden the battery's operating temperature.
[0129] In some embodiments, the cyclic ether compound comprises one or more selected from 1,3-dioxolane, tetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
[0130] The cyclic polymers readily undergo a ring-opening reaction at room temperature under the initiation of Lewis acids, making the in-situ polymerization process highly reliable. The reaction materials can be added during the battery injection process, allowing the in-situ polymerization to be completed before the battery leaves the factory, eliminating the need for additional time or steps, further improving production efficiency.
[0131] In some embodiments, the solvent comprises a chain ether compound.
[0132] In this article, the term "chain ether compound" refers to a product in which the hydrogen in the hydroxyl group of an alcohol or phenol is replaced by a hydrocarbon group, and the carbon atoms and oxygen atoms in the product are connected to each other in a chain.
[0133] Chain ether compounds give the electrolyte a suitable viscosity and excellent ionic conductivity. At the same time, chain ether compounds and polyethers have the same ether bond, which can improve the compatibility of the electrolyte system and make the polyether evenly distributed in the electrolyte, which helps to improve the battery's initial coulombic efficiency, room temperature cycle performance and high temperature cycle performance, reduce the battery's high temperature gas production, improve the battery's electrochemical performance and safety performance, and broaden the battery's operating temperature.
[0134] The molecules of chain ether compounds can construct a stable electrode / electrolyte interface on the surface of the negative electrode of sodium metal batteries (including the negative electrode of batteries without negative electrode), carbon material negative electrodes and other non-carbon material negative electrodes, forming a stable solid electrolyte interface (SEI), reducing electrochemical polarization, and improving the battery's first coulombic efficiency and high-temperature cycle performance.
[0135] Taking sodium metal batteries as an example, ether solvents have good compatibility with alkali metal negative electrodes. They can effectively passivate sodium metal and form a thin, uniform and dense SEI film on the surface of sodium metal, further preventing the formation of sodium dendrites and preventing the SEI film from further thickening due to the growth and evolution of sodium dendrites, thereby affecting the conduction of ions.
[0136] In this article, the term "anode-free battery" refers to a battery that uses a current collector as the anode during assembly. During the charging process, metal ions are deposited on the current collector to form a metal anode.
[0137] In some embodiments, the solvent comprises one or more selected from ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether.
[0138] In some embodiments, the volume content of the cyclic ether compound added is 1 / 5-5 based on the total volume of the solvent in the electrolyte. In some embodiments, the volume content of the cyclic ether compound added is any one of 1 / 4-4, 2 / 7-3.5, 1 / 3-3, 2 / 5-2.5, 1 / 2-2, and 2 / 3-1.5 based on the total volume of the solvent in the electrolyte.
[0139] The appropriate volume content of cyclic ether compounds ensures that the ring-opening reaction can proceed smoothly, so that the electrolyte has an appropriate mass content of polyether, while ensuring that the electrolyte has suitable viscosity and excellent ionic conductivity, reducing the high-temperature gas production of the battery, and ensuring that the battery has excellent first coulombic efficiency, room temperature cycle performance and high-temperature cycle performance.
[0140] In some embodiments, the volume content of the cyclic ether compound added is 1 / 3-3 based on the total volume of the solvent in the electrolyte. In some embodiments, the volume content of the cyclic ether compound added is optionally any one of 1 / 3-3, 2 / 5-2.5, 1 / 2-2, and 2 / 3-1.5 based on the total volume of the solvent in the electrolyte.
[0141] The appropriate volume content of cyclic ether compounds ensures that the ring-opening reaction can proceed smoothly, so that the electrolyte has an appropriate mass content of polyether, while ensuring that the electrolyte has suitable viscosity and excellent ionic conductivity, further reducing the high-temperature gas production of the battery, and ensuring that the battery has excellent first coulombic efficiency, room temperature cycle performance and high-temperature cycle performance.
[0142] In some embodiments, the electrolyte salt includes at least one of a first sodium salt and a second sodium salt, the first sodium salt includes one or more selected from sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, and sodium trifluoroacetate, and the anion structure of the second sodium salt includes at least one of the structures shown in Formula I and Formula II.
[0143]
[0144] wherein R1, R2, and R3 are each independently fluorine or a C1-C6 fluoroalkyl group.
[0145] As used herein, the term "C1-C6 fluoroalkyl" refers to an alkane having one to six carbon atoms substituted with at least one fluorine.
[0146] In some embodiments, the second sodium salt comprises one or more selected from the group consisting of sodium fluorosulfonate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, and sodium (fluorosulfonyl)(trifluoromethanesulfonyl)imide.
[0147] In some embodiments, the second sodium salt comprises one or two selected from sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethanesulfonyl)imide.
[0148] The weak binding force between the anions and sodium ions in the first sodium salt facilitates rapid deposition and stripping of metal ions, improving the battery's kinetic performance. Particularly in a battery without a negative electrode, the second sodium salt can effectively maintain the battery's capacity and cycle performance. The second sodium salt optimizes the deposition and stripping of metal ions, improving the cycle performance of secondary batteries. Furthermore, the appropriate concentrations of the first and second sodium salts provide the electrolyte with suitable viscosity and excellent ionic conductivity, enhancing the overall electrochemical performance of the secondary battery.
[0149] The anions in the second sodium salt have a strong binding force with the sodium ions, making them more easily incorporated into the electrolyte salt's solvation structure. This allows them to easily deposit metal ions on the negative electrode surface, where they are reduced to form an SEI composed primarily of sulfides and nitrides. This significantly improves the structural stability and uniformity of the SEI on the secondary battery surface. On the one hand, an SEI containing a large amount of sulfides and nitrides is less susceptible to secondary decomposition and regeneration, reducing metal consumption within the battery and improving the high-temperature cycling performance of the secondary battery. On the other hand, a structurally stable and uniformly distributed SEI reduces direct contact between the electrolyte and the metal, thereby reducing side reactions between the electrolyte and the metal, inhibiting gas generation during high-temperature cycling, and improving high-temperature gassing in secondary batteries.
[0150] In some embodiments, the electrolyte salt includes a first sodium salt.
[0151] The electrolyte contains the first sodium salt, the battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance, and the battery has low high temperature gas production.
[0152] In some embodiments, the electrolyte salt includes a second sodium salt.
[0153] The electrolyte contains the second sodium salt, and the battery has low high-temperature gas generation.
[0154] In some embodiments, the electrolyte salt includes a first sodium salt and a second sodium salt.
[0155] The electrolyte contains a first sodium salt and a second sodium salt, which ensures that the metal ions can be reversibly deposited and stripped, while also ensuring the generation of a structurally stable and uniformly distributed SEI, thereby improving the high-temperature cycle performance of the secondary battery and improving the high-temperature gas production performance of the secondary battery.
[0156] In some embodiments, the mass content of the first sodium salt in the electrolyte is 2% to 40% based on the total mass of the electrolyte. In some embodiments, the mass content of the first sodium salt in the electrolyte can be any one of 2% to 10%, 2% to 20%, 2% to 30%, 10% to 20%, 10% to 30%, 10% to 40%, 20% to 30%, 20% to 40%, and 30% to 40% based on the total mass of the electrolyte.
[0157] The first sodium salt with an appropriate mass content ensures the reversible deposition and stripping of metal ions, while making the electrolyte have suitable viscosity and excellent ionic conductivity, which can improve the battery's initial coulombic efficiency and room temperature cycle performance, and reduce the battery's high-temperature gas production.
[0158] In some embodiments, the mass content of the second sodium salt in the electrolyte is 1% to 10% based on the total mass of the electrolyte. In some embodiments, the mass content of the second sodium salt in the electrolyte can be any one of 1% to 2%, 1% to 4%, 1% to 6%, 1% to 8%, 1% to 10%, 2% to 4%, 2% to 6%, 2% to 8%, 2% to 10%, 4% to 6%, 6% to 8%, 6% to 10%, and 8% to 10%, based on the total mass of the electrolyte.
[0159] The second sodium salt with an appropriate mass content is helpful to form a structurally stable and evenly distributed SEI, which can improve the high-temperature cycle performance of the battery and reduce the high-temperature gas production of the battery.
[0160] In some embodiments, the viscosity of the electrolyte at 25° C. is less than 1300 mPa·s. In some embodiments, the viscosity of the electrolyte at 25° C. can be selected from 1.5 mPa·s to 200 mPa·s, 1.5 mPa·s to 400 mPa·s, 1.5 mPa·s to 600 mPa·s, 1.5 mPa·s to 800 mPa·s, 1.5 mPa·s to 1000 mPa·s, 1.5 mPa·s to 1200 mPa·s, 200 mPa·s to 400 mPa·s, 200 mPa·s to 400 mPa·s, 200 mPa·s to 600 mPa·s, 200 mPa·s to 800 mPa·s, 200 mPa·s to 1000 mPa·s, 1.5 mPa·s to 12 ... Any one of Pa·s to 1000mPa·s, 200mPa·s to 1300mPa·s, 400mPa·s to 600mPa·s, 400mPa·s to 800mPa·s, 400mPa·s to 1000mPa·s, 400mPa·s to 1300mPa·s, 600mPa·s to 800mPa·s, 600mPa·s to 1000mPa·s, 600mPa·s to 1300mPa·s, 800mPa·s to 1000mPa·s, and 800mPa·s to 1300mPa·s.
[0161] The viscosity of the electrolyte can be tested in any known manner. For example, a rheometer is used to measure the viscosity of the electrolyte at 25°C.
[0162] The electrolyte with appropriate viscosity makes the electrolyte have excellent ionic conductivity, and at the same time makes the electrolyte have good wettability to the electrodes, ensuring good contact between the electrolyte and the electrodes and improving the electrochemical performance of the battery.
[0163] In some embodiments, the electrolyte further comprises other solvents in addition to the chain ether compound solvent. Non-limiting examples of other solvents include at least one selected from vinylene carbonate, ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0164] In some embodiments, the electrolyte may optionally include additional additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve thermal stability of the electrolyte, and the like.
[0165] [Method for preparing electrolyte]
[0166] The present application also provides a method for preparing a secondary battery electrolyte, comprising the following steps: adding an additive and a cyclic ether compound to a composition comprising an electrolyte salt and a solvent, wherein the additive is a Lewis acid or a Lewis acid precursor; and in situ polymerization for at least 24 hours to obtain a secondary battery electrolyte.
[0167] In this article, the term "Lewis acid precursor" refers to a chemical substance that can generate Lewis acid under certain conditions. The conditions that trigger the Lewis acid precursor to generate Lewis acid can be thermal decomposition, chemical reaction, or photoinitiation.
[0168] In some embodiments, the polymerization temperature is any one of 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, and 60°C.
[0169] In some embodiments, the polymerization time is any one of 24 hours, 36 hours, 48 hours, 60 hours, and 72 hours.
[0170] The above polymerization conditions are mild and the reaction time is controllable, which makes the in-situ polymerization low in cost and high in efficiency, and is conducive to industrial promotion and use.
[0171] Lewis acids or Lewis acid precursors are used to initiate in-situ polymerization of cyclic ether compounds, generating uniformly distributed polyethers. The resulting polyethers provide a polymer backbone that can bind solvent molecules, thereby reducing the kinetic activity of solvent molecules in the electrolyte, minimizing direct contact between the positive and negative electrodes and the solvent, and lowering the likelihood of chemical reactions between the positive and negative electrodes and the solvent. This suppresses gas generation during high-temperature cycling of the secondary battery, improves the high-temperature gas generation performance of the secondary battery, and enhances the safety of the secondary battery at high temperatures.
[0172] In some embodiments, the additive comprises one or more selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate.
[0173] Under certain conditions, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate decompose to produce Lewis acids, which are used to initiate the polymerization of cyclic ether compounds to form polyethers. These lithium salts also provide a certain amount of lithium ions, which can improve the battery's room-temperature and high-temperature cycling performance and reduce high-temperature gassing.
[0174] In some embodiments, the Lewis acid comes from an additive in the electrolyte, and the additive comprises one or two selected from lithium hexafluorophosphate and lithium tetrafluoroborate.
[0175] Lithium hexafluorophosphate and lithium tetrafluoroborate are prone to thermal decomposition, which makes in-situ polymerization easy to occur and can ensure the reliability of the reaction.
[0176] Suitable additives can improve the room temperature cycle performance and high temperature cycle performance of the battery and reduce the high temperature gas production of the battery.
[0177] In some embodiments, based on the total mass of the electrolyte, the mass content of the additives added is 1% to 10%. In some embodiments, based on the total mass of the electrolyte, the mass content of the additives added can be 1% to 2%, 1% to 3%, 1% to 4%, 1% to 5%, 1% to 6%, 1% to 7%, 1% to 8%, 1% to 9%, 1% to 10%, 2% to 3%, 2% to 4%, 2% to 5%, 2% to 6%, 2% to 7%, 2% to 8%, 2% to 9%, 2% to 10%, 3% to 4%, 3% to 5%, 3% to 6%, 3% to 7%, 3%-8%, 3%-9%, 3%-10%, 4%-5%, 4%-6%, 4%-7%, 4%-8%, 4%-9%, 4%-10%, 5%-6%, 5%-7%, 5%-8%, 5%-9%, 5%-10%, 6%-7%, 6%-8%, 6%-9%, 6%-10%, 7%-8%, 7%-9%, 7%-10%, 8%-9%, 8%-10%, 9%-10%.
[0178] The appropriate mass content of additives makes the electrolyte have suitable viscosity and good ionic conductivity. The battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance and low high temperature gas production, which can further broaden the operating temperature of the battery.
[0179] In some embodiments, the mass content of the additive added is 2% to 6% based on the total mass of the electrolyte. In some embodiments, the mass content of the additive added is any one of 2% to 3%, 2% to 4%, 2% to 5%, 2% to 6%, 3% to 4%, 3% to 5%, 3% to 6%, 4% to 5%, 4% to 6%, and 5% to 6% based on the total mass of the electrolyte.
[0180] Additives with appropriate mass content can improve the battery's initial coulombic efficiency, room temperature cycle performance and high temperature cycle performance, and reduce the battery's high temperature gas production.
[0181] In some embodiments, the cyclic ether compound comprises one or more selected from 1,3-dioxolane, ethylene glycol diglycidyl ether, 1,4-butanediol glycidyl ether, 1,2,3,4-diepoxybutane, tetrahydrofuran, methyltetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
[0182] Suitable cyclic ether compounds are easy to undergo ring-opening polymerization, which is conducive to the occurrence of in-situ polymerization reactions. By generating polyethers with appropriate mass content, the electrolyte has suitable viscosity and good ionic conductivity. The battery has excellent first coulombic efficiency, room temperature cycle performance, high temperature cycle performance and low high temperature gas production, which can further broaden the battery's operating temperature.
[0183] In some embodiments, the cyclic ether compound comprises one or more selected from 1,3-dioxolane, tetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
[0184] The cyclic polymers readily undergo a ring-opening reaction at room temperature when initiated by a Lewis acid, making the in-situ polymerization highly reliable. The in-situ polymerization reaction can be completed during the battery packaging process, eliminating the need for additional time or steps, further improving production efficiency.
[0185] In some embodiments, the volume content of the cyclic ether compound added is 1 / 5-5 based on the total volume of the solvent in the electrolyte. In some embodiments, the volume content of the cyclic ether compound added is any one of 1 / 4-4, 2 / 7-3.5, 1 / 3-3, 2 / 5-2.5, 1 / 2-2, and 2 / 3-1.5 based on the total volume of the solvent in the electrolyte.
[0186] The appropriate volume content of cyclic ether compounds can ensure the mass content of polyether in the electrolyte, so that the electrolyte has suitable viscosity and excellent ionic conductivity, reduce the high-temperature gas production of the battery, and ensure that the battery has excellent first coulombic efficiency, room temperature cycle performance and high-temperature cycle performance.
[0187] In some embodiments, the volume content of the cyclic ether compound added is 1 / 3-3 of the total volume of the solvent in the electrolyte. In some embodiments, the volume content of the cyclic ether compound added is any one of 1 / 3-3, 2 / 5-2.5, 1 / 2-2, and 2 / 3-1.5 of the total volume of the solvent in the electrolyte.
[0188] The appropriate volume content of cyclic ether compounds can ensure the mass content of polyether in the electrolyte, so that the electrolyte has suitable viscosity and excellent ionic conductivity, reduce the high-temperature gas production of the battery, and ensure that the battery has excellent first coulombic efficiency, room temperature cycle performance and high-temperature cycle performance.
[0189] [Secondary battery]
[0190] The present application also provides a secondary battery, comprising an electrolyte, wherein the electrolyte comprises the electrolyte in any embodiment or the electrolyte prepared by the preparation method in any implementation.
[0191] In some embodiments, the secondary battery includes at least one of a sodium ion battery and a lithium ion battery.
[0192] In some embodiments, the secondary battery is a negative electrode-less sodium metal battery.
[0193] In this article, the term "anode-free sodium metal battery" refers to a sodium metal battery that uses a current collector as the anode during the assembly process. During the charging process of the anode-free sodium metal battery, sodium ions are deposited on the current collector to form a sodium metal anode.
[0194] In anode-free sodium metal batteries, the metallic sodium on the negative electrode is generated during subsequent cycles. Sodium-ion batteries have no voltage before the first charge, allowing them to be stored for long periods without self-discharge. Even if the battery is short-circuited, no current is generated, resulting in extremely high safety. Because the negative electrode current collector surface is devoid of negative electrode active material and only uses the negative electrode current collector, the battery can achieve a higher energy density.
[0195] In some embodiments, a secondary battery includes a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector and a primer layer formed on at least a portion of a surface of the negative electrode current collector.
[0196] The primer layer has the characteristic of low metal nucleation potential, which can effectively improve the metal deposition / dissolution performance. At the same time, it can also improve the huge volume changes caused by the metal deposition / dissolution process to the battery cell, stabilize the battery cell structure, improve the high-temperature cycle performance of the battery, and reduce the high-temperature gas production of the battery.
[0197] In some embodiments, the negative electrode current collector used in the negative electrode sheet includes at least one of a metal foil current collector, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, and a carbon paper current collector. Sodium ions do not form alloys with aluminum. Based on the considerations of cost reduction and weight reduction, sodium ion batteries preferably use aluminum-based current collectors. The aluminum-based current collector is any one of aluminum foil, aluminum alloy foil and aluminum-based composite current collector. The aluminum-based composite current collector includes a polymer base film and aluminum foil and / or aluminum alloy foil formed on both sides of the polymer base film. Specifically, the aluminum-based composite current collector has a "sandwich" structure, with the polymer base film located in the middle and aluminum foil provided on both sides, or aluminum alloy foil provided on both sides. It can also be that aluminum foil is provided on one side of the polymer base film and aluminum alloy foil is provided on the other side. The polymer base film is any one of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, poly(p-phenylene terephthalamide), polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate.
[0198] In some embodiments, the primer layer comprises a binder, and the binder comprises any one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, lithium / sodium polyacrylate, polytetrafluoroethylene, polyimide, and polyurethane.
[0199] In some embodiments, the base coating is a metal coating, the metal has a body-centered cubic structure, and the metal includes any one of α-Fe, V, Nb, Cr, Mo, Ta, and W.
[0200] In some embodiments, the base coating is an alloy coating, and the alloy includes any one metal of Au, Ag, Sn, Sb or an alloy composed of multiple metals.
[0201] In some embodiments, the base coating is a metal oxide coating, and the oxide includes at least one of copper oxide and aluminum oxide.
[0202] In some embodiments, the primer layer is a conductive polymer coating, and the conductive polymer includes any one of polyaniline, polythiophene, polypyrrole, and polyphenylene vinylene.
[0203] In some embodiments, the base coating is a conductive ceramic coating, and the conductive ceramic material includes at least one of TiB2, TiC, and B4C3.
[0204] In some embodiments, the primer layer is a conductive carbon coating, and the conductive carbon includes at least one of conductive carbon black, graphite, carbon fiber, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and fullerene.
[0205] Conductive carbon coating can effectively reduce the overpotential of metal deposition, inhibit the formation of metal dendrites, improve the room temperature cycle performance and high temperature cycle performance of the battery, and reduce the high temperature gas production of the battery.
[0206] In some embodiments, the surface density of the conductive carbon coating is 5 to 50 g / m 2 In some embodiments, the surface density of the conductive carbon coating may be 5 to 10 g / m 2 , 5~20g / m 2 , 5~30g / m 2 , 5~40g / m 2 , 5~50g / m 2 , 10~20g / m 2 , 10~30g / m 2 , 10~40g / m 2 、 10~50g / m 2 , 20~30g / m 2 , 20~40g / m 2 , 20~50g / m 2 30~40g / m 230~50g / m 2 , 40~50g / m 2 Any one of .
[0207] A suitable range of undercoat surface density can optimize metal deposition, improve the battery's Coulombic efficiency and cycle performance, and reduce high-temperature gassing. At the same time, a suitable range of undercoat surface density can increase the battery's energy density and meet battery usage requirements.
[0208] [Positive electrode]
[0209] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material may include at least one of a layered transition metal oxide, a polyanionic compound, and a Prussian blue compound.
[0210] The transition metal in the layered transition metal oxide can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Optionally, the layered transition metal oxide is, for example, NaxMO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, and 0<x≤1.
[0211] Polyanionic compounds can be metal ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The metal ion can be selected from sodium ion, lithium ion, potassium ion, and zinc ion; the transition metal can be selected from at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be selected from at least one of P, S, and Si; n represents (YO4) n- valence.
[0212] Prussian blue compounds can be compounds containing sodium ions, transition metal ions, and cyanide ions (CN-). The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0213] The positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The conductive agent may be selected from one or more of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.
[0214] The positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and optional conductive agent to the positive electrode current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA), and carboxymethyl chitosan (CMCS).
[0215] The positive electrode current collector can be a conductive carbon sheet, metal foil, carbon-coated metal foil, porous metal plate, or a composite current collector. The conductive carbon material of the conductive carbon sheet can be selected from one or more of Super P, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers. The metal material of the metal foil, carbon-coated metal foil, and porous metal plate can each be independently selected from at least one of copper, aluminum, nickel, and stainless steel. The composite current collector can be a composite of metal foil and a polymer-based film.
[0216] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0217] [Isolation film]
[0218] In some embodiments, the sodium ion battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0219] In some embodiments, the material of the separator can be selected from at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fibers. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0220] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0221] In some embodiments, the sodium ion battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0222] In some embodiments, the outer packaging of the sodium ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the sodium ion battery can also be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, and examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0223] The present application has no particular limitation on the shape of the sodium ion battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a sodium ion battery 5 having a square structure as an example.
[0224] In some embodiments, referring to FIG2 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the sodium ion battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0225] In some embodiments, sodium ion batteries can be assembled into a battery module. The number of sodium ion batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0226] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple sodium-ion batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple sodium-ion batteries 5 may be secured using fasteners.
[0227] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of sodium ion batteries 5 are received in the receiving space.
[0228] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0229] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0230] In addition, the present application also provides an electrical device, which includes at least one of the sodium ion battery, battery module, or battery pack provided in the present application. The sodium ion battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0231] As the electrical device, a sodium ion battery, a battery module or a battery pack can be selected according to its usage requirements.
[0232] Figure 6 shows an example of an electric device. This device can be a pure electric vehicle, hybrid electric vehicle, or plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the sodium-ion battery in this device, a battery pack or battery module can be used.
[0233] Another example device may be a mobile phone, a tablet computer, a laptop computer, etc. Such a device is generally required to be lightweight and thin, and may use a sodium ion battery as a power source.
[0234] Example
[0235] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0236] 1. Preparation method
[0237] Example
[0238] Example 1
[0239] 1) Preparation of electrolyte
[0240] In an argon atmosphere glove box with a water content of less than 10 ppm, the first sodium salt, sodium hexafluorophosphate, and the second sodium salt, sodium bis(fluorosulfonyl)imide, were added to a solvent of ethylene glycol dimethyl ether. After stirring, lithium hexafluorophosphate and 1,3-dioxolane were added as additives. Based on the total weight of the electrolyte, the weight content of lithium hexafluorophosphate was 4%, the weight content of sodium bis(fluorosulfonyl)imide was 5%, and the weight content of sodium hexafluorophosphate was 15%. The electrolyte was in situ polymerized at room temperature (23-27°C) for 48 hours to obtain a secondary battery electrolyte.
[0241] 2) Preparation of positive electrode sheet
[0242] The positive electrode active material Na3V2(PO4)3, the binder polyvinylidene fluoride (PVDF), and the conductive agent conductive carbon black (Super-P) are mixed in N-methylpyrrolidone (NMP) solvent in a mass ratio of 96%:2%:2% to prepare the positive electrode slurry. The positive electrode slurry is coated on the surface of aluminum foil by an extrusion coating machine according to the mass requirement of the positive electrode active material per unit area and dried. The coated electrode is then pressed by a cold press at a pressure of 2.5g / cm 3 The designed compaction is cold pressed to prepare the final positive electrode sheet.
[0243] 3) Preparation of negative electrode sheet
[0244] Add carbon nanotubes and sodium alginate into water and stir to form a uniform slurry. The slurry is coated on the negative electrode current collector, dried and cut to obtain a negative electrode sheet without a negative electrode structure. The surface density of the base coating is 10g / m 2 ;
[0245] 4) Isolation film
[0246] Polyethylene film (PE film) is used as the separator.
[0247] 5) Preparation of batteries
[0248] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets to serve as an isolation layer. The electrolyte is then added to form a button battery.
[0249] Examples 2 to 4
[0250] The battery preparation methods of Examples 2 to 4 are similar to those of Example 1, except that lithium hexafluorophosphate is replaced by aluminum chloride, aluminum perchlorate, and lithium tetrafluoroborate, respectively. The specific adjustment parameters are shown in Table 1 below.
[0251] Examples 5 to 8
[0252] The battery preparation methods of Examples 5 to 8 are similar to those of Example 1, but the mass content of lithium hexafluorophosphate in the electrolyte is adjusted. The specific adjustment parameters are shown in Table 1 below.
[0253] Examples 9 to 11
[0254] The battery preparation methods of Examples 9 to 11 are similar to those of Example 1, except that 1,3-dioxolane is replaced by tetrahydropyran, tetrahydrofuran, and 1,4-dioxane, respectively. The specific adjustment parameters are shown in Table 1 below.
[0255] Example 12
[0256] The battery preparation method of Example 12 is similar to that of Example 1, except that ethylene glycol dimethyl ether is replaced with dimethyl carbonate. The specific adjustment parameters are shown in Table 1 below.
[0257] Examples 13 to 18
[0258] The battery preparation methods of Examples 13 to 18 are similar to those of Example 1, but the volume content of 1,3-dioxolane in the electrolyte is adjusted. The specific adjustment parameters are shown in Table 1 below.
[0259] Example 19
[0260] The battery preparation method of Example 19 is similar to that of Example 1, except that sodium bis(fluorosulfonyl)imide is replaced with sodium hexafluorophosphate, that is, the mass content of sodium hexafluorophosphate in the electrolyte is 20%. The specific adjustment parameters are shown in Table 1 below.
[0261] Example 20
[0262] The battery preparation method of Example 20 is similar to that of Example 1, except that sodium hexafluorophosphate is replaced with sodium bis(fluorosulfonyl)imide, that is, the mass content of sodium bis(fluorosulfonyl)imide in the electrolyte is 20%. The specific adjustment parameters are shown in Table 1 below.
[0263] Examples 21 to 24
[0264] The battery preparation methods of Examples 21 to 24 are similar to those of Example 1, but the mass content of sodium hexafluorophosphate in the electrolyte is adjusted. The specific adjustment parameters are shown in Table 1 below.
[0265] Examples 25-26
[0266] The battery preparation methods of Examples 25 to 26 are similar to those of Example 1, except that sodium bis(fluorosulfonyl)imide is replaced by sodium trifluoromethanesulfonate and sodium bis(trifluoromethanesulfonyl)imide, respectively. The specific adjustment parameters are shown in Table 1 below.
[0267] Examples 27 to 30
[0268] The battery preparation methods of Examples 27 to 30 are similar to those of Example 1, but the mass content of sodium bis(fluorosulfonyl)imide in the electrolyte is adjusted. The specific adjustment parameters are shown in Table 1 below.
[0269] Example 31
[0270] The battery preparation method of Example 31 is similar to that of Example 1, but the preparation process of the negative electrode sheet is adjusted. Carbon nanotubes and sodium alginate are added to water and stirred into a uniform slurry. The slurry is coated on the negative electrode current collector, dried, and cut to obtain a negative electrode current collector with a primer layer, wherein the surface density of the primer layer is 10 g / m 2 ; The negative electrode active material hard carbon, the conductive agent acetylene black, the binder styrene-butadiene rubber (SBCs), and the thickener hydroxymethyl cellulose (CMC) are fully stirred and mixed in an appropriate amount of deionized water in a weight ratio of 90:5:4:1 to form a uniform negative electrode slurry; the negative electrode slurry is applied to the negative electrode collector with a primer layer, dried at 100°C, and pressed to obtain a negative electrode sheet. The specific adjustment parameters are shown in Table 1 below.
[0271] Example 32
[0272] The battery preparation method of Example 32 is similar to that of Example 1, but the negative electrode plate is replaced with aluminum foil. The specific adjustment parameters are shown in Table 1 below.
[0273] Example 33
[0274] The battery preparation method of Example 33 is similar to that of Example 31, but the carbon nanotubes are replaced with aluminum oxide. The specific adjustment parameters are shown in Table 1 below.
[0275] Examples 34 to 37
[0276] The battery preparation methods of Examples 34 to 37 are similar to those of Example 1, but the surface density of the bottom coating layer of the negative electrode plate is adjusted. The specific adjustment parameters are shown in Table 1 below.
[0277] Example 38
[0278] The battery preparation method of Example 38 is similar to that of Example 1, but the mass content of lithium hexafluorophosphate in the electrolyte is adjusted. The specific adjustment parameters are shown in Table 1 below.
[0279] Example 39
[0280] The battery preparation method of Example 39 is similar to that of Example 1, but the mass content of sodium hexafluorophosphate in the electrolyte is adjusted. The specific adjustment parameters are shown in Table 1 below.
[0281] Comparative Example 1
[0282] The battery preparation method of Comparative Example 1 is similar to that of Example 1, but the electrolyte does not contain lithium hexafluorophosphate and 1,3-dioxolane. The specific adjustment parameters are shown in Table 1 below.
[0283] Comparative Example 2
[0284] The battery preparation method of Comparative Example 2 is similar to that of Comparative Example 1, except that the solvent is replaced with dimethyl carbonate. The specific adjustment parameters are shown in Table 1 below.
[0285] Comparative Example 3
[0286] The battery preparation method of Comparative Example 3 is similar to that of Comparative Example 1, but the mass content of sodium hexafluorophosphate in the electrolyte is adjusted. The specific adjustment parameters are shown in Table 1 below.
[0287] Comparative Example 4
[0288] The battery preparation method of Comparative Example 4 is similar to that of Comparative Example 3, except that ethylene glycol dimethyl ether is replaced by dimethyl carbonate.
[0289] Comparative Example 5
[0290] The battery preparation method of Comparative Example 5 is similar to that of Example 1, but the electrolyte does not contain 1,3-dioxolane. The specific adjustment parameters are shown in Table 1 below.
[0291] Comparative Example 6
[0292] The battery preparation method of Comparative Example 6 is similar to that of Example 33, but the electrolyte does not contain lithium hexafluorophosphate and 1,3-dioxolane. The specific adjustment parameters are shown in Table 1 below.
[0293] Comparative Example 7
[0294] The battery preparation method of Comparative Example 7 is similar to that of Comparative Example 6, but the mass content of sodium hexafluorophosphate in the electrolyte is adjusted. The specific adjustment parameters are shown in Table 1 below.
[0295] Comparative Example 8
[0296] The preparation method of the battery of Comparative Example 8 is similar to that of Example 1, except that the lithium hexafluorophosphate in the electrolyte is replaced with sodium hexafluorophosphate. The specific adjustment parameters are shown in Table 1 below.
[0297] 2. Performance Testing
[0298] The performance test method is as follows:
[0299] 1. Polyether
[0300] 1) Detection of polyether
[0301] Disassemble the battery, extract the polymerized electrolyte, and use a Thermo Scientific infrared spectrometer in reflection mode to collect the spectrum of the extracted electrolyte. - 1 ~900cm -1 (such as 850cm -1The long chain vibration infrared peak of the polymer main chain appears near 950cm -1 ~1050cm -1 (e.g. 1000cm -1 If the vibration peak of COC appears near the electrolyte, it can be determined that the electrolyte contains polyether.
[0302] 2) Mass content of polyether
[0303] The battery cell was disassembled and the electrolyte was extracted. 5 mg of the polymerized electrolyte was dissolved and dispersed in tetrahydrofuran by ultrasonication. The resulting dispersion was then subjected to gel permeation chromatography to determine the mass of the polyether in the electrolyte or the mass content of the polyether based on the total mass of the electrolyte.
[0304] 2. Electrolyte
[0305] 1) Lithium ion mass content
[0306] The electrolyte in the battery is obtained by centrifugation, and the mass content of lithium ions based on the total mass of the electrolyte is obtained by ion chromatography.
[0307] 2) Viscosity of the electrolyte
[0308] The viscosity of the electrolyte at 25 ° C was measured using a rheometer. At 25 ° C and normal pressure (0.1 MPa), the shear rate of the instrument was set to 0.1s -1 -300s -1 The electrolyte is sheared to obtain viscosity curves at different shear rates, and the obtained viscosity values are read.
[0309] 3) Ionic conductivity of the electrolyte
[0310] Measure the ionic conductivity of the electrolyte using a conductivity meter at 25°C and atmospheric pressure (0.1 MPa). Rinse the conductivity electrode with deionized water and rinse with anhydrous ethanol to remove any residual moisture. Once the electrode is dry, insert it into a test tube containing the electrolyte to be tested, ensuring that the platinum electrode is submerged in the electrolyte. Once the instrument reading stabilizes, record the result. Repeat the measurement three times and calculate the average value.
[0311] 3. Battery
[0312] 1) First Coulombic efficiency test
[0313] At 25°C and normal pressure (0.1MPa), the battery was charged to 3.5V at a constant current rate of 0.1C. The charging capacity at this time was recorded as the first charging capacity of the battery. After that, it was allowed to stand for 5 minutes, and then discharged at a constant current rate of 0.1C to 3.2V. It was allowed to stand for 5 minutes. The discharge capacity at this time was recorded as the first discharge capacity of the battery. The first coulombic efficiency of the battery (%) = first discharge capacity / first charging capacity × 100%.
[0314] 2) Normal temperature cycle performance
[0315] At 25°C and atmospheric pressure (0.1MPa), the battery was charged at a constant current of 0.5C to a voltage of 3.5V, and then discharged at a constant current of 1C to a voltage of 3.2V. This constituted one charge-discharge cycle. The charge-discharge cycle was repeated 500 times, with the initial discharge capacity set as 100%. The test was then stopped and the cycle capacity retention rate was recorded. The capacity retention rate was used as an indicator to evaluate the battery's cycling performance.
[0316] 3) High temperature cycle performance
[0317] At 60°C and atmospheric pressure (0.1MPa), the battery was charged at a constant current of 0.5C to a voltage of 3.5V, and then discharged at a constant current of 1C to a voltage of 3.2V. This constituted one charge-discharge cycle. The charge-discharge cycle was repeated 500 times, with the initial discharge capacity set as 100%. The test was then stopped and the cycle capacity retention rate was recorded. The capacity retention rate was used as an indicator to evaluate the battery's cycling performance.
[0318] 4) High temperature gas production performance
[0319] At room temperature (25°C), charge the battery to 3.5V at a constant current of 0.5C. After the battery is fully charged, the initial volume of the battery is tested by the drainage method. After the battery is stored in an oven at 60°C for 24 days, take out the battery. Let it stand for 60 minutes at room temperature. Test the battery volume by the drainage method within 60 minutes after cooling to room temperature. Calculate the battery volume expansion rate based on the battery volume tested before storage. The volume expansion rate (%) of the battery after storage at 60°C for 24 days = (battery volume measured after storage / battery volume measured before storage) - 1.
[0320] 3. Analysis of test results of various embodiments and comparative examples
[0321] Batteries of various examples and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Table 1 below.
[0322] Table 1 Preparation parameters and test results of Examples and Comparative Examples
[0323]
[0324]
[0325]
[0326] The above results indicate that the secondary battery electrolytes in Examples 1-39 include an electrolyte salt, a solvent, and a polyether. The electrolytes include a first sodium salt of sodium hexafluorophosphate and / or a second sodium salt of any one of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethanesulfonyl)imide. The solvent is ethylene glycol dimethyl ether or dimethyl carbonate. The polyether includes any one of poly-1,3-dioxolane, polytetrahydropyran, polytetrahydrofuran, and poly-1,4-dioxane. Comparison of Examples 1-11 and 13-39 with Comparative Examples 1, 3, and 5-8, and Example 12 with Comparative Examples 2 and 4, demonstrates that electrolytes containing polyethers can reduce the high-temperature expansion rate of the battery, minimize high-temperature gassing, and improve battery safety.
[0327] Comparing Examples 1, 3, and 4 with Example 2, it can be seen that the electrolyte contains lithium ions with a lithium ion content of 0.05% to 0.46% by mass, based on the total mass of the electrolyte, which can improve the room temperature cycle performance and high temperature cycle performance of the battery and reduce the high temperature gas production of the battery. It can be seen from Examples 1, 5 to 8, and 38 that the electrolyte contains lithium ions with a lithium ion content of 0.05% to 0.46% by mass, based on the total mass of the electrolyte, that the battery has excellent room temperature cycle performance and high temperature cycle performance, and low high temperature gas production.
[0328] As can be seen from Examples 1 and 13 to 18, when the mass content of polyether is 10% to 70% based on the total mass of the electrolyte, the battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature performance, low high temperature gas production, and widens the operating temperature of the battery.
[0329] As can be seen from Examples 1 to 39, the polyether is generated by in-situ polymerization of cyclic ether compounds in the electrolyte under the initiation of any one of the Lewis acids of phosphorus pentafluoride, aluminum trichloride, lithium chloride, and boron trifluoride, which can reduce the high-temperature gas generation of the battery.
[0330] From the comparison between Examples 1, 3, and 4 and Example 2, it can be seen that the Lewis acid comes from the additive in the electrolyte, and the additive includes one or more selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate, which can improve the room temperature cycle performance and high temperature cycle performance of the battery and reduce the high temperature gas production of the battery.
[0331] From the comparison between Examples 1 and 4 and Example 3, it can be seen that the Lewis acid comes from the additive in the electrolyte, and the additive includes one or two selected from lithium hexafluorophosphate and lithium tetrafluoroborate, which improves the room temperature cycle performance and high temperature cycle performance of the battery and reduces the high temperature gas production of the battery.
[0332] It can be seen from Examples 1, 5 to 8, and 38 that, based on the total mass of the electrolyte, the mass content of the additives added is 1% to 10%, the electrolyte has a suitable viscosity and good ionic conductivity, the battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance and low high temperature gas production, the battery has excellent electrochemical properties and safety performance, and broadens the operating temperature of the battery.
[0333] From the comparison between Examples 1, 6, and 7 and Examples 5 and 8, it can be seen that the mass content of the additives added is 2% to 6% based on the total mass of the electrolyte, which can improve the battery's initial coulombic efficiency, room temperature cycle performance, and high temperature cycle performance, and reduce the battery's high-temperature gas production.
[0334] As can be seen from Examples 1 and 9 to 11, the cyclic ether compound includes one or more selected from 1,3-dioxolane, ethylene glycol diglycidyl ether, 1,4-butanediol glycidyl ether, 1,2,3,4-diepoxybutane, tetrahydrofuran, methyltetrahydrofuran, 1,4-dioxane, and tetrahydropyran. The electrolyte has a suitable viscosity and good ionic conductivity, the battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance and low high temperature gas production, the battery has excellent electrochemical performance and safety performance, and the battery's operating temperature is broadened.
[0335] From the comparison between Example 1 and Example 12, it can be seen that the solvent contains a chain ether compound, which can increase the viscosity of the electrolyte, improve the initial coulombic efficiency, room temperature cycle performance and high temperature cycle performance of the battery, reduce the high temperature gas production of the battery, improve the electrochemical performance and safety performance of the battery, and broaden the operating temperature of the battery.
[0336] From the comparison between Examples 1, 14 to 17 and Examples 13 and 18, it can be seen that the volume content of the cyclic ether compound added is 1 / 5-5 of the total volume of the solvent in the electrolyte, which reduces the high-temperature gas production of the battery. At the same time, the electrolyte has a suitable viscosity and good electrical conductivity, and the battery maintains excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance.
[0337] From the comparison of Examples 1, 15 to 16 with Examples 13 to 14, 17 to 18, it can be seen that the volume content of the cyclic ether compound added is 1 / 3-3 of the total volume of the solvent in the electrolyte, which can further reduce the high-temperature gas production of the battery. At the same time, the electrolyte has a suitable viscosity and good electrical conductivity, and the battery maintains excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance.
[0338] It can be seen from Examples 1 and 19 to 20 that the electrolyte contains at least one of the first sodium salt sodium hexafluorophosphate and the second sodium salt sodium bis(fluorosulfonyl)imide, and the battery has low high-temperature gas generation.
[0339] As can be seen from Examples 1 and 19, the electrolyte contains the first sodium salt sodium hexafluorophosphate, the battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance, and the battery has low high temperature gas production.
[0340] It can be seen from Examples 1 and 20 that the electrolyte contains the second sodium salt sodium bis(fluorosulfonyl)imide, and the battery has low high-temperature gas generation.
[0341] From the comparison between Example 1 and Examples 19 to 20, it can be seen that the electrolyte contains the first sodium salt sodium hexafluorophosphate and the second sodium salt sodium bis(fluorosulfonyl)imide, which can improve the battery's initial coulombic efficiency, room temperature cycle performance and high temperature cycle performance, and reduce the high-temperature gas production of the battery.
[0342] From the comparison of Examples 1, 22, 23, and 39 with Examples 21 and 24, it can be seen that the mass content of the first sodium salt sodium hexafluorophosphate in the electrolyte is 2% to 40% based on the total mass of the electrolyte, which can improve the initial coulombic efficiency and room temperature cycle performance of the battery and reduce the high-temperature gas production of the battery.
[0343] It can be seen from Examples 1, 25, and 26 that the second sodium salt comprises one or more selected from sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethanesulfonyl)imide, and the battery has excellent first coulombic efficiency, room temperature cycle performance and high temperature cycle performance, low high temperature gas production, and widens the operating temperature of the battery.
[0344] From the comparison of Examples 1, 28 to 29 with Examples 27 and 30, it can be seen that the mass content of the second sodium salt in the electrolyte is 1% to 10% based on the total mass of the electrolyte, which can improve the high-temperature cycle performance of the battery and reduce the high-temperature gas production of the battery.
[0345] It can be seen from Examples 1 to 37 that the viscosity of the electrolyte at 25° C. is less than 1300 mPa·s, and the electrolyte has appropriate viscosity and good ionic conductivity.
[0346] From the comparison between Example 1 and Example 31, it can be seen that the secondary battery is a negative electrode-free sodium metal battery, which can improve the room temperature cycle performance and high temperature cycle performance of the battery and reduce the high temperature gas production phenomenon of the battery.
[0347] From the comparison between Examples 1 and 33 and Example 32, it can be seen that the negative electrode plate includes a negative electrode current collector and a primer layer formed on at least a portion of the surface of the negative electrode current collector, which can improve the high-temperature cycle performance of the battery and reduce the high-temperature gas production of the battery.
[0348] From the comparison between Example 1 and Example 33, it can be seen that the bottom coating is a conductive carbon coating, which can improve the room temperature cycle performance and high temperature cycle performance of the battery and reduce the high temperature gas production phenomenon of the battery.
[0349] From the comparison between Examples 1, 34-35 and Examples 36-37, it can be seen that the surface density of the conductive carbon coating is 5-50 g / m 2 , which can improve the room temperature cycle performance and high temperature cycle performance of the battery and reduce the high temperature gas production of the battery.
Claims
1. A secondary battery electrolyte, characterized in that Includes electrolyte salt, solvent and polyether.
2. The electrolyte according to claim 1, characterized in that The electrolyte contains lithium ions, and the mass content of the lithium ions is 0.05% to 0.46% based on the total mass of the electrolyte.
3. The electrolyte according to claim 1 or 2, characterized in that The mass content of the polyether is 10% to 70%, based on the total mass of the electrolyte.
4. The electrolyte according to any one of claims 1 to 3, characterized in that The polyether is generated by in-situ polymerization of cyclic ether compounds in an electrolyte under the initiation of Lewis acid.
5. The electrolyte according to claim 4, characterized in that The Lewis acid comes from an additive in the electrolyte, and the additive includes one or more selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium difluorooxalatoborate, and can be one or two of lithium hexafluorophosphate and lithium tetrafluoroborate.
6. The electrolyte according to claim 5, characterized in that Based on the total mass of the electrolyte, the mass content of the additive is 1% to 10%, and can be optionally 2% to 6%.
7. The electrolyte according to any one of claims 4 to 6, characterized in that The cyclic ether compound includes one or more selected from 1,3-dioxolane, ethylene glycol diglycidyl ether, 1,4-butanediol glycidyl ether, 1,2,3,4-diepoxybutane, tetrahydrofuran, methyltetrahydrofuran, 1,4-dioxane, and tetrahydropyran, and can be selected from one or more of 1,3-dioxolane, tetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
8. The electrolyte according to any one of claims 1 to 7, characterized in that The solvent comprises a chain ether compound.
9. The electrolyte according to any one of claims 1 to 8, characterized in that The solvent comprises one or more selected from ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether.
10. The electrolyte according to any one of claims 4 to 9, characterized in that Based on the total volume of the solvent in the electrolyte, the volume content of the cyclic ether compound added is 1 / 5-5, and can be optionally 1 / 3-3.
11. The electrolyte according to any one of claims 1 to 10, characterized in that The electrolyte salt includes at least one of a first sodium salt and a second sodium salt, wherein the first sodium salt includes one or more selected from sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, and sodium trifluoroacetate, and the anion structure of the second sodium salt includes at least one of the structures shown in Formula I and Formula II. wherein R1, R2, and R3 are each independently fluorine or a C1-C6 fluoroalkyl group.
12. The electrolyte according to claim 11, characterized in that Based on the total mass of the electrolyte, the mass content of the first sodium salt in the electrolyte is 2% to 40%.
13. The electrolyte according to claim 11 or 12, characterized in that The second sodium salt comprises one or more selected from the group consisting of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethanesulfonyl)imide.
14. The electrolyte according to any one of claims 11 to 13, characterized in that Based on the total mass of the electrolyte, the mass content of the second sodium salt in the electrolyte is 1% to 10%.
15. The electrolyte according to any one of claims 1 to 14, characterized in that The viscosity of the electrolyte at 25° C. is less than 1300 mPa·s.
16. A method for preparing a secondary battery electrolyte, characterized in that: The following steps are involved: Adding an additive and a cyclic ether compound to a composition comprising an electrolyte salt and a solvent, wherein the additive is a Lewis acid or a Lewis acid precursor; The in-situ polymerization is carried out for at least 24 hours to obtain the secondary battery electrolyte.
17. The preparation method according to claim 16, characterized in that The additive comprises one or more selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium difluorooxalatoborate, aluminum chloride, and aluminum trifluoromethanesulfonate, and can be one or two of lithium hexafluorophosphate and lithium tetrafluoroborate.
18. The preparation method according to claim 16 or 17, characterized in that: Based on the total mass of the electrolyte, the mass content of the additive is 1% to 10%, and can be optionally 2% to 6%.
19. The preparation method according to any one of claims 16 to 18, characterized in that The cyclic ether compound includes one or more selected from 1,3-dioxolane, ethylene glycol diglycidyl ether, 1,4-butanediol glycidyl ether, 1,2,3,4-diepoxybutane, tetrahydrofuran, methyltetrahydrofuran, 1,4-dioxane, and tetrahydropyran, and can be selected from one or more of 1,3-dioxolane, tetrahydrofuran, 1,4-dioxane, and tetrahydropyran.
20. The preparation method according to any one of claims 16 to 19, characterized in that Based on the total volume of the solvent in the electrolyte, the volume content of the cyclic ether compound added is 1 / 5-5, and can be optionally 1 / 3-3.
21. A secondary battery, characterized in that: The invention comprises an electrolyte, wherein the electrolyte comprises the electrolyte according to any one of claims 1 to 15 or the electrolyte prepared by the preparation method according to any one of claims 16 to 20.
22. The secondary battery according to claim 21, wherein The secondary battery includes at least one of a sodium ion battery and a lithium ion battery.
23. The secondary battery according to claim 21 or 22, characterized in that: The secondary battery is a negative electrode-free sodium metal battery.
24. The secondary battery according to any one of claims 21 to 23, characterized in that The secondary battery includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a primer layer formed on at least a portion of the surface of the negative electrode current collector.
25. The secondary battery according to claim 24, characterized in that The primer layer is a conductive carbon coating.
26. The secondary battery according to claim 25, characterized in that The surface density of the conductive carbon coating is 5 to 50 g / m 2 .
27. A battery module, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 21 to 26.
28. A battery pack, characterized in that: The invention comprises at least one of the secondary battery according to any one of claims 21 to 26 and the battery module according to claim 27.
29. An electrical device, characterized in that: The battery comprises at least one selected from the group consisting of the secondary battery according to any one of claims 21 to 26, the battery module according to claim 27, and the battery pack according to claim 28.
Citation Information
Cited By
Electrolyte for negative-electrode-free sodium ion battery and negative-electrode-free sodium ion battery
CN122552627A
Electrolyte, sodium metal battery cell, battery apparatus, and electric apparatus
WO2026144914A1